2015
DOI: 10.1080/02643294.2014.995075
|View full text |Cite
|
Sign up to set email alerts
|

Support for distinct subcomponents of spatial working memory: A double dissociation between spatial–simultaneous and spatial–sequential performance in unilateral neglect

Abstract: Over the last decade, many studies have demonstrated that visuo-spatial working memory (VSWM) can be divided into separate subsystems dedicated to the retention of visual patterns and their serial order. Impaired VSWM has been suggested to exacerbate left visual neglect in rightbrain damaged individuals. The aim of this study was to investigate the segregation between spatial-sequential and spatial-simultaneous working memory in individuals with neglect. We demonstrated that patterns of results on these VSWM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 65 publications
2
12
0
1
Order By: Relevance
“…Therefore, a general impairment of keeping track of the spatial codes associated with ordinal information, irrespective of whether they are represented in the neglected or intact space, could explain why we observed a non-lateralized deficit of serial order in our patients. Finally, Wansard et al (2015) observed that simultaneous and sequential aspects of spatial working memory can be selectively impaired in patients with neglect. Because many similarities exist when memorizing the serial order of verbal and visuo-spatial information in working memory (for a review, see Hurlstone, Hitch, & Baddeley, 2014), it would therefore be interesting to investigate whether impairments of serial order in patients with neglect are systematically observed in both verbal and visuospatial working memory.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, a general impairment of keeping track of the spatial codes associated with ordinal information, irrespective of whether they are represented in the neglected or intact space, could explain why we observed a non-lateralized deficit of serial order in our patients. Finally, Wansard et al (2015) observed that simultaneous and sequential aspects of spatial working memory can be selectively impaired in patients with neglect. Because many similarities exist when memorizing the serial order of verbal and visuo-spatial information in working memory (for a review, see Hurlstone, Hitch, & Baddeley, 2014), it would therefore be interesting to investigate whether impairments of serial order in patients with neglect are systematically observed in both verbal and visuospatial working memory.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, Wansard et al . () observed that simultaneous and sequential aspects of spatial working memory can be selectively impaired in patients with neglect. Because many similarities exist when memorizing the serial order of verbal and visuo‐spatial information in working memory (for a review, see Hurlstone, Hitch, & Baddeley, ), it would therefore be interesting to investigate whether impairments of serial order in patients with neglect are systematically observed in both verbal and visuo‐spatial working memory.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of sequential or simultaneous presentation of stimuli on performance have been recently described in children with a nonverbal (visuospatial) learning disability (NLD) and in patients with unilateral neglect (Mammarella et al, 2009;Wansard et al, 2015), showing a dissociation according to sequential and simultaneous presentation modality. Specifically, whereas patients affected by unilateral neglect performed worse when the stimuli were presented sequentially than when they were presented simultaneously, children with NLD showed the opposite behavior (Mammarella et al, 2009;Wansard et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…C. Mammarella et al, 2006;N. Mammarella, Cornoldi, & Donadello, 2003;Piccardi et al, 2011;Wansard et al, 2015).…”
unclassified
“…Several arguments in relation to simultaneous and sequential processes in visuospatial working memory have arisen: simultaneous and sequential processes might be regarded as indicators of visual and spatial working memory, respectively (Oosterman, Morel, Meijer, Buvens, Kessels, & Postma, 2011); alternatively, simultaneous and sequential processes might be distinguished in spatial working memory (Pazzaglia & Cornoldi, 1999). Nevertheless, a range of experimental (Della Sala, Gray, Baddeley, Allamano, & Wilson, 1999;Frick, 1985), developmental (Hamilton, Coates, & He ernan, 2003;Logie & Pearson, 1997), and decit studies (Mammarella, Cornoldi, Pazzaglia, Toso, Grimoldi, & Vio, 2006;Wansard, Bartolomeo, Bastin, Segovia, Gillet, Duret, & Meulemans, 2015) have found evidence for the distinction between simultaneous and sequential processes in visuospatial working memory.…”
Section: Introductionmentioning
confidence: 99%